PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KINERJA INDIVIDUAL PADA SEKTOR PERBANKAN (Studi Kasus pada BRI Cabang Temanggung ) - Agung Dwi Susilo; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2016)
This research aims to determine the effect of the use of information technology are described with indicators of social factors, affect, complexity, Job Fit, long – term consequences, and Facilitating Conditions the performance of individual employees BRI branch of Temanggung. It also aims to provide empirical evidence of the existence of a positive relationship between the use of information technology through the indicators of social factors, affect, complexity, Job Fit, long – term consequences, and Facilitating Conditions the performance of individual employees BRI branch of Temanggung.This research uses the BRI branch employee population in Temanggung. The sample was 65 respondents. Testing the hypothesis in this study using multiple linear regression analysis.The result of this study indicate that social factors, affcet, and job fit no significant positive effect on the dependent variable. It means that the environmental conditions and feelings of users who do not support. Long – term consequences to take effect positive and significant. This is because employees feel technology useful information for the future. While the complexity and the facilitating conditions the negative and no significant. This is because the company’s environmental circumstances unfavorable utilization as well as individuals who find it difficult in the use of information technology.